RANCANG BANGUN SISTEM INFORMASI LAYANAN REKAM MEDIS PRAKTIK DOKTER GIGI BERSAMA DI TABING - Annisa Aulia Zaroh; Dedy Irfan; Elfi Tasrif (Universitas Negeri Padang, 2017)
The most important thing in the medical world is entering a history of the patient’s health, and this is known as the medical records. The medical records patients are used as references to the doctor for examination of the patient’s health, as well as records of a diagnosis of a disease patients and medical services. According to with the purpose of this final task, to provide design data supporting the medical records is complete and structured to facilitate action. The design of this web based information system using the codeigniter framework, programming PHP (Hypertext Preprocessor) with XAMPP as a Database Management System (DBMS), and sublime Text 3 as editor. Medical record service information system providing data supporting a complete medical record and structured in order to facilitate doing of medical, simplify data searches of patient medical record along with its report. The design of this information systems is performed to produce an information system that can create your medical record is tored neatly and securely in a database, facilitate the search process patient medical record data when data is needed, minimize errors in data processing of patient medical record. The design of the information system displays data, patient medical record, making the reference and the doctor's license. Keywords : Medical Record, Web, PHP